Perlindungan Hukum Bagi Tenaga Kesehatan Terhadap Kekerasan di Fasilitas Pelayanan Kesehatan - Baba, Amiruddin Islami MQ.; Bondi, Adi Papa Jefrianto; Manda, Bakri K.; Indrawan, Rudy; Sitorus, Novandrik Yeriko (Media Hukum Indonesia (MHI), 2025)
Violence in healthcare is a serious and increasing phenomenon, occurring in physical, verbal, and psychological forms, perpetrated by patients, their families, and others. This violence not only negatively impacts healthcare workers in the form of trauma, stress, decreased work motivation, and psychological disorders, but also impacts the quality of care and patient safety. This study uses a normative juridical method with a legislative approach through a literature review to examine the forms of violence, causal factors, impacts, and the effectiveness of legal protection for healthcare workers. The results show that although regulations related to the protection of healthcare workers are available, such as Law Number 36 of 2014 concerning Healthcare Workers and Law Number 17 of 2023 concerning Health, implementation in the field still faces obstacles, including weak law enforcement, minimal outreach, and limited security systems in healthcare facilities. Therefore, legal protection does not stop at providing regulations but must be realized through concrete actions, such as strengthening security, providing complaint channels, legal assistance, and educating the public about patient rights and obligations. With these steps, legal protection for healthcare workers can be implemented more effectively, creating a safe and conducive work environment that supports improved healthcare quality.